Lexicon and its Essential Subtypes in English Language - Jurayeva Zulaykho Shamshiddinovna (Peerian Journals Publishing, 2022)
Over recent years there has been much interest in the sphere of distributional semantics, focusing on the distributional hypothesis: words that occur in similar contexts tend to have similar meanings (Harris, 1954). There is a large body of work on the use of different similarity measures (Lee, 1999; Weeds and Weir, 2003; Curran, 2004) and many researchers have built thesauri (i.e., lists of “nearest neighbours”) automatically and applied them in a variety of applications, generally with a good deal of success.
Keywords: hyponyms; hypernyms; co-hyponyms